The effect of applied electric field on the micromorphology of Pt nanoparticles synthesized by laser ablation. Issue 12 (26th July 2021) - Bakhtiari, Mohammad; Hantehzadeh, Mohammadreza; Darabi, Elham
Abstract: In the present study, laser ablation technique (Nd:YAG) has been applied to synthesize platinum nanoparticles (NPs). Also, the effect of applied electric field on the physical, structural, and morphological properties of Pt NPs has been investigated during the nanosecond pulsed laser ablation of platinum. Based on the results extracted from TEM and scanning electron microscopy images, the formation of high percentage of NPs with spherical shape is demonstrated in all samples. The increase of applied electric field creates few rectangular, hexagonal, and rhombic NPs with the average size decreased from 20 to 9 nm. The significant influence of increasing electric field is also observed in UV–vis spectra by appearing the blue shift of the localized surface plasmon resonance peak. The UV–vis spectra also confirm the metallic nature of Pt NPs and the existence of inhomogeneous‐sized particles and the coagulation of particle because of the long tail in higher wavelengths. In addition, atomic force microscopy images have been analyzed through MountainsMap Premium program and fractal dimension. As can be seen, increasing the applied electric field make the surface more irregular and the maximum value of D f reveals the most irregular topography for sample with 50 V/cm electric field. Finally, the bending and stretching frequencies of the functional bending groups connected to the NPs surface have been characterized by Fourier transform infrared spectroscopy. Electrical field‐assisted laser ablation in liquids method allows a better control of the size, morphology, structure, and chemical composition of nanoparticles. Abstract : Platinum nanoparticles have been synthesized by laser ablation method (Nd:YAG). The effect of applied electric field on the micromorphology of Pt NPs has been investigated by analyzing atomic force microscopy and Scanning electron microscopy images. The optical and structural properties of Pt NPs and the influence of applied electric field on them are studied through UV–vis spectra, energy‐dispersive X‐ray, X‐ray diffraction, and Fourier transform infrared analysis. The size distribution and shape of samples with different applied electric fields are compared by valuable information extracted from TEM images.